SIFAT PAPAN WOL KAYU DARI 19 JENIS KAYU SULAWESI TENGAH - l M Sulastiningsih; Paribotro Sutigno; Rozak Memed (Pusat Penelitian dan Pengembangan Hasil Hutan, 1987)
The results of laboratory test on the properties of wood-wood boards manufactured from 19 individual wood species obtained from Central Sulawesi province are reported in this paper. The tests comprised board density, moisture content, thickness reduction due to compression and bending strength.The results show an average yield of wood-wool is 238 kg per cubic meter of log input. Four wood species required presoaking for wood-wool making. The physical and mechanical properties of the wood-woo/ board made from seven wood species mineralized with CaCl2 solution or Ca(OH2) suspension meet DIN 1101 standard.